Glucosinolate-rich broccoli sprouts protect against oxidative stress and improve adaptations to intense exercise training - Flockhart, M.; Nilsson, L.C.; Tillqvist, E.N.; Vinge, F.; Millbert, F.; Lännerström, J.; Nilsson, P.H.; Samyn, D.; Apró, W.; Sundqvist, M.L.; Larsen, F.J. (Redox biology, 2023)
Oxidative stress plays a vital role for the adaptive responses to physical training. However, excessive oxidative stress can precipitate cellular damage, necessitating protective mechanisms to mitigate this effect. Glucosinolates, found predominantly in cruciferous vegetables, can be converted into isothiocyanates, known for their antioxidative properties. These compounds activate crucial antioxidant defence pathways and support mitochondrial function and protein integrity under oxidative stress, in both Nrf2-dependent and independent manners. We here administered glucosinolate-rich broccoli sprouts (GRS), in a randomized double-blinded cross-over fashion to 9 healthy subjects in combination with daily intense exercise training for 7 days. We found that exercise in combination with GRS significantly decreased the levels of carbonylated proteins in skeletal muscle and the release of myeloperoxidase into blood. Moreover, it lowered lactate accumulation during submaximal exercise, and attenuated the severe nocturnal hypoglycaemic episodes seen during the placebo condition. Furthermore, GRS in combination with exercise improved physical performance, which was unchanged in the placebo condition.